Kontribusi Sektor Kehutanan Terhadap Pembangunan Daerah Provinsi Kalimantan Selatan (Pendekatan Perhitungan PDRB Hijau) - Muhammad Anshar Nur; Ahmad Yunani; Siti Mutmainah Zulfaridatul Yaqin (Ecoplan, 2018)
This study aims to determine and analyze the contribution of the forestry sector to the development of the province of South Kalimantan in 2012 - 2016 by using the Green GRDP calculation approach. The study uses a descriptive method with quantitative data processing on secondary data supported by primary data through the calculation value for unit rent, depletion, degradation and depreciation of logs harvesting activities in natural forest and plantation forest. The results of the study show that the value of unit rent, depletion, degradation and depreciation per unit of production in natural forest is relatively much greater than that of plantation forest. This value is around 81 % in natural forest and 9 % in plantation forest, so it is necessary to intensify the management of plantation forest for the supply of logs as well as an effort to reduce pressure on natural forest in South Kalimantan. The green contribution of the forestry sector to regional development is smaller or less than the contribution of the forestry sector in the calculation of conventional GRDP, which means that the province of South Kalimantan has sacrificed assets (natural capital) from depreciation of forest resources that have not been calculated as added value of the forestry sector in the calculation of conventional GRDP. The value of forestry sector revenue as the value of compensation and incentives from the value of forest and environmental resource depreciation is relatively very small compared to the value needed for prevention and recovery. The contribution (value added) of the real forestry sector to the development of the province of South Kalimantan by including the value of depreciation of forest resources is around 119 % of the GRDP listed in conventional GRDP. Keywords: Green GRDP, Forestry Sector, Harvesting of Logs, Natural Forest, Plantation Forest